Routine treatment pathways of patients with major depression and active suicidal ideation with intent in Italy: interim results from the ARIANNA observational study. (1st June 2022) - Pompili, M.; Bellomo, A.; Pilotto, E.; Rosso, G.; Adami, M.; Andreis, D.; Roncari, B.; Delmonte, D.
Abstract : Introduction: Major depressive disorder (MDD), especially in case of suicidal risk, is a psychiatric emergency, associated with high patient burden and healthcare resource utilization. Although active and urgent treatment is crucial, little is known on comprehensive care management of this condition in Italy. Objectives: Here we report the ARIANNA study [NCT04463108] interim results to primarily describe the treatment utilization pathways of patients with MDD and active suicidal ideation with intent in the current clinical practice in Italy. Methods: This observational prospective cohort study included adult patients with a moderate-to-severe major depressive episode (MDE) and active suicidality from 24 Italian sites. Real-world data on patient characteristics, treatments, clinical outcomes, and healthcare utilization were collected during a 90-day follow-up. Data collection is still ongoing. Results: Sixty-four evaluable patients were considered for this interim analysis: 41 (64.1%) females, mean [SD] age 46.0 [15.4] years, a concomitant psychiatric diagnosis in 7 (10.9%), and other comorbidities in 26 (40.6%). The baseline mean [SD] MADRS total score was 37.5 [7.2], with severe MDE and prior suicidal behavior in 30 (46.9%) and 21 (32.8%) patients, respectively. Median [25th;75th percentiles] duration of current MDE was 1.1 [0.3;2.1] months. Acute inpatient hospitalization was provided for 43 (67.2%) patients. Antidepressant augmentation with mood stabilizers and/or antipsychotic drugs and optimization were the most frequent early standard-of-care treatment regimens in 32 (53.3%) and 24 (40.0%) patients with available data (N=60), respectively. Conclusions: Our preliminary results suggest that initial treatment approaches in this critical population are mostly polypharmacological and delivered as inpatient care, with consequent intensive resource utilization. Disclosure: The ARIANNA study was sponsored by Janssen-Cilag SpA, Italy. DD and MA are employees of Janssen-Cilag SpA. DA and BR are employees of MediNeos S.U.R.L., a company subject to the direction and coordination of IQVIA Solutions HQ Ltd.